A General Solution for Eccentric Loads on Weld Groups - Brandt, G. Donald (Engineering Journal, 1982)
Eccentric loads on weld groups traditionally have been analyzed by elastic methods in which the individual effects of an axial load (applied through the centroid of the weld group) and a pure moment (in the plane of the weld group) were combined. In the 7th Edition Manual of Steel Construction of the American Institute of Steel Construction, as in earlier editions, such a procedure was used to create tables which could be used to determine allowable eccentric loads on selected weld groups. These tables were criticized as having non-uniform factors of safety when compared to the actual ultimate loads which the welds could support. An "ultimate strength method" was proposed in which the resulting force per unit of length of each weld element is calculated.